Use of emulsifier and lipase in feeds for broiler chickens - Oliveira, Lennon Santos de; Balbino, Eric Márcio; Silva, Tamiris Natalice Santos; Ily, Lin; Rocha, Tatiana Cristina da; Strada, Evani Souza de Oliveira; Pinheiro, Alexandre Moraes; Brito, Jeronimo Avito Gonçalves de (Semina: Ciências Agrárias, 2019)
The objective of this study was to evaluate the effect of exogenous emulsifier and lipase in diets on performance, digestibility, and organ biometry of broiler chickens. A completely randomised design with seven treatments and seven replications was adopted. The treatments were as follows: T1 (positive control; PC): 3000, 3100, 3200, and 3250 Kcal of metabolisable energy (ME) kg-1 of diet for phases 1 to 10, 11 to 21, 22 to 31, and 32 to 37 days, respectively; T2: PC with reduction in ME of 30 Kcal kg-1 of diet; T3: PC with reduction in ME of 60 Kcal kg-1 of feed; T4 (negative control; NC): PC with reduction in ME of 90 Kcal kg-1 of feed; T5: NC with inclusion of exogenous lipase (10 000 U kg-1); T6: NC with inclusion of emulsifier (250 g t-1); and T7: NC with inclusion of lipase (10 000 U kg-1) and emulsifier (250 g t-1) in the period from 1 to 37 days of rearing. Performance characteristics (weight gain (WG), feed intake (FI), and feed conversion (FC)), carcass yield, cut yield, the relative weight of abdominal fat and organs (small intestine, liver, and pancreas), and relative intestinal length, in addition to dry matter digestibility (CDADM), ethereal extract (CDAEE), crude metabolisable energy (CMACE), and apparent metabolisable energy (AME) of the diets, were evaluated. In the initial phase, the CDAEE was higher for the PC group than for the emulsifier + lipase group. The AME determined in the final phase for the group supplemented with an emulsifier was higher by approximately 50 Kcal (EM) than the NC group. The WG of the lipase group was similar to that of the PC group. However, the groups with emulsifier and emulsifier + lipase showed a lower WG than the PC group. The additives used did not recover the FC to the same level observed in the PC group. The reduction in ME of 90 Kcal kg-1 generated a lower WG and worse FC. The use of both an emulsifier and lipase together produced results like to the PC group. The biometrics of the organs and the carcass yield and cuts were not influenced by diets. Thus, it can be concluded that the inclusion of lipase and an emulsifier improves the performance of broilers given diets with reduced energy, although it does not improve the lipid utilisation of the diets.